2007
DOI: 10.1080/08860220601039551
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Kaposi's Sarcoma Following Treatment of Membranoproliferative Glomerulonephritis and a Review of the Literature

Abstract: Kaposi's sarcoma (KS) is an unusual tumor principally affecting the skin of the lower extremities. Although the association between KS and renal transplant has been well documented, there are a few KS cases in the literature associated with membranoproliferative glomerulonephritis or other glomerular diseases. This report presents a patient with membranoproliferative glomerulonephritis (MPGN) who developed KS following treatment with long-term medium dose glucocorticoid and short-term additional immunosuppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Our study has shown four-fold odds of Kaposi's sarcoma-related mortality in individuals receiving glucocorticoids, after controlling for possible confounding factors. Glucocorticoid therapy has also been clinically associated with development of Kaposi's sarcoma in non-HIV-related diseases such as transplant recipients [ 14 , 15 ]; rheumatic disorders [ 16 , 17 ]; asthma [ 18 ]; lung cancer [ 19 ]; dermatologic diseases [ 20 , 21 ]; atopic dermatitis [ 22 ]; ulcerative colitis [ 23 ]; glomerulonephritis [ 24 , 25 ] and many other clinical conditions of iatrogenic immunosuppression. In most cases, withdrawal of immunosuppressive therapies leads to Kaposi's sarcoma remission, but not in the case of HIV-infected individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown four-fold odds of Kaposi's sarcoma-related mortality in individuals receiving glucocorticoids, after controlling for possible confounding factors. Glucocorticoid therapy has also been clinically associated with development of Kaposi's sarcoma in non-HIV-related diseases such as transplant recipients [ 14 , 15 ]; rheumatic disorders [ 16 , 17 ]; asthma [ 18 ]; lung cancer [ 19 ]; dermatologic diseases [ 20 , 21 ]; atopic dermatitis [ 22 ]; ulcerative colitis [ 23 ]; glomerulonephritis [ 24 , 25 ] and many other clinical conditions of iatrogenic immunosuppression. In most cases, withdrawal of immunosuppressive therapies leads to Kaposi's sarcoma remission, but not in the case of HIV-infected individuals [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persons with chronic renal failure are at risk of developing HHV8-related diseases, and KS is a rare complication of glomerular diseases (Agbaht et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…KS has been rarely reported to be associated with glomerulonephritis with and without the use of immunosuppressive therapy. [8][9][10][11][12] The mechanism of pathogenesis is thought to be reactivation of latent HHV-8 infection. The underlying kidney disease has no role in development of KS as it was seen in different diseases such as membranoproliferative, focal glomerulosclerosis, as well as membranous glomerulonephritis.…”
Section: Discussionmentioning
confidence: 99%
“…It was also seen in the usage of cyclophosphamide and azathioprin. 12 In these cases, the patients usually develop a cutaneous KS. In contrast to that, our patient unusually developed a tonsillar tumor.…”
Section: Discussionmentioning
confidence: 99%